MATLAB prime - Sigmon, Kermit (CRC Press, 1994)
This Fourth Edition reflects an extensive general revision of the MATLAB Primer into a more compact, reader-friendly bound format. However, its hands-on approach retains the original purpose of the earlier editions-to help students and others begin to use MATLAB.